Evaluation of the bioherbicidal potential of tree species collected in remnants of the Andean forests - ORTIZ LOPEZ, Juan José; LOBO ECHEVERRI, Tatiana (Revista Productos Naturales, 2022)
Being Colombia a megadiverse country, its native species have been little explored as an alternative source of bioactive compounds that help mitigate problems caused by synthetic products.